Molecular imaging biomarkers for breast cancer risk and personalized screening - Besutti, Giulia; Iotti, Valentina; Rossi, Paolo Giorgi (Translational Cancer Research, 2018)
Recently, Hruska and colleagues (1) published an interesting paper in Breast Cancer Research on a crucial topic to understanding breast cancer risk factors. In 2016, they assessed BPU with molecular breast imaging (MBI) as a risk factor through a case-control study nested in a cohort study (2); in their recent study they showed that a semi-automated system can be used for a quantitative measurement of BPU (1).